Risky sexual behavior and associated factors among preparatory school students in Arsi Negelle Town Oromia, Ethiopia - Nega Degefa Megersa; Girum Sebsibe Teshome (Intelektual Pustaka Media Utama, 2020)
Risky sexual behavior remains the major public concern commonly affecting youths. These behaviors lead to undesirable health outcomes including sexually transmitted infections, unplanned pregnancy and abortion for female. This study was intended to assess risky sexual behavior and associated factors among preparatory school students in Arsi Negelle Town. Institution-based cross-sectional study was conducted among 300 preparatory school students. Data was collected using a structured and pre-tested questionnaire. Bivariate and multivariable analysis was conducted to identify the association between variables. Statistical significance was declared at p<0.05. The prevalence of risky sexual behavior was, 32. % (95% CI: 24.3, 40.9). It was significantly associated with students grade level (AOR: 5.77; 95% CI: 1.49, 22.28), having no discussion on sexual and reproductive health (AOR: 11.28; 95% CI: 1.8, 77.49), poor knowledge on HIV/AIDS (AOR: 4.86, 95% CI: 1.38, 17.11), not watching porn movies (AOR: 0.01; 95% CI: 0.001, 0.26), having pocket money (AOR: 0.10; 95% CI: 0.03, 0.39) and having peer influence (AOR: 0.07; 95% CI: 0.02, 0.28). Significant number of students engaged in at least one risky sexual behavior. The behavior was commonly seen among students with poor knowledge about HIV, no discussion on sexual and reproductive health, lower grade level, having pocket money, having peer influence and watching pornographic movies.